Real-Time Parallel Programming for Homogeneous Multicores - Pinho, Luis Miguel (International Symposium on Industrial Embedded Systems (Online), 2024)
Developing real-time systems applications requires programming paradigms that can handle the specification of concurrent activities and timing constraints, and controlling execution on a particular platform. The increasing need for high-performance, and the use of fine-grained parallel execution, makes this an even more challenging task. This paper explores the state-of-the-art and challenges in real-time parallel application development, focusing on two research directions: one from the high-performance domain (using OpenMP) and another from the real-time and critical systems field (based on Ada). The paper reviews the features of each approach and highlights remaining open issues.